GENDER REPRESENTATION ON THE TEXT OF ARTICLES IN THE NEWSPAPERS - Alemina Br. Perangin-angin; Masdiana Lubis; Ely Hayati Nasution; Tasnim Lubis; Zurriyati A. Jalil (LLDIKTI Wilayah X, 2021)
Since March 2020, the Government has enforced Large-Scale Social Restrictions (PSBB) in various red zones to minimize the number of Covid-19 cases, to work from home or live at home might bring additional issues, such as violence against women, in the latest situation. During the COVID-19 pandemic, newspapers play a vital role in reporting occurrences of female assault. .This article focuses on examining how women are exposed to violence in Indonesia during the current pandemic of coronavirus (COVID-19) from Critical Discourse Analysis. This research aimed to discover the Critical Discourse Analysis of newspaper articles that deal with violence against women. The articles is qualitative research, reported based on content analysis techniques. This research contributes to the analysis of media representation of women by providing context-sensitive results of the phenomena that occurred in women during the COVID-19 pandemic. The findings reveal the stability of discursive structures over time, especially gender bias in women's media representation during the COVID-19 pandemic. Women are still affected by gender bias due to the patriarchal, social, and culture that exists in Indonesia. The newspapers can provide a clear picture of women. This research by the Critical Discourse Analysis investigates how the BBC.com news, VOAindonesia.com texts reveal their meaning, while the newspapers reported women's existence as marginalizing, the BBC.com news, VOAindonesia.com, were also the courage to raise women's image as marginalizing.